Respiratory Mycopathogens: A study of mycological, risk factors, clinical profiles and antifungal resistance pattern in a tertiary health care centre in the foothills of Himalaya - Dr Amber Prasad; Dr Priyal Anand; Dr Mukesh Bairwa; Dr Uttam Kumar Nath; Dr Smita Sinha; Dr PV Sowjanya; Dr Yogendra Pratap Mathuria (International Journal of Infectious Diseases)
India faces a significant burden of respiratory fungal infections, yet many cases remain underdiagnosed particularly in rural and remote areas. This leads to higher morbidity and mortality rates, especially among immunocompromised individuals. The unique environmental conditions of the Himalayan foothills further complicate the detection and management of these infections.This study was conducted in the Department of Microbiology at All India Institute of Medical Sciences, Rishikesh, for a period of 18 months, from October 2022 to March 2024. The aim of the study was to characterise the clinical, risk factors, susceptibility and outcome profile of invasive bronchopulmonary fungal infections among patients attending AIIMS Rishikesh.Out of the total bronchopulmonary fungal Infections (n=61), 85% cases (n=52) were those of invasive aspergillosis due to Aspergillus spp. with the most common species being A. fumigatus (n=36), followed by A. flavus (n=12), A. terreus (n=2), A. glaucus (n=1), A. niger (n=1). Apart from this, pulmonary mucormycosis was seen in 6% (n=4) of the cases, due to Mucor spp. (n=2), Rhizopus arrhizus (n=1) and Lichthemia corymbifera (n=1). 8% (n=5) of the cases of invasive fungal infections due to rarer fungi, Curvularia lunata (n=1), Scedosporium apiospermum (n=1), Fusarium solani (n=1), Bipolaris spp (n=1), and Penicillium spp. (n=1). The most common risk factor was chronic uncontrolled diabetes mellitus (n=24), COPD/Asthma/ILD (n=22), hypertension (n=18), pulmonary tuberculosis (n=15), different malignancies (n=10) and CAD (n=10). Out of the 61 cases, 52% n=32) patients were discharged with follow up, 32% (n=20) patients succumbed to death, 9% (n=6) cases were treated on an outpatient basis and 6% cases(n=3) patients went left against medical advice. 49% (n=30) required ICU stay during the course of treatment. Aspergillus spp were resistant to iatraconazole and caspofungin with high MIC (8-16).Voricoanzole showed lower MICs (0.06-2) and was preferred for the treatment as well.The study's findings on the high prevalence of invasive aspergillosis (85%) align with global and regional studies, which also identify Aspergillus fumigatus as the leading cause of respiratory fungal infections, especially in immunocompromised patients. Like other research, this study highlights emerging antifungal resistance, with high MICs for itraconazole and caspofungin, underscoring the growing preference for voriconazole due to its lower MICs and better efficacy. Additionally, the presence of rarer fungi like Curvularia and Scedosporium suggests regional variations in pathogen distribution, influenced by local environmental factors in the Himalayan foothills, a trend noted in other endemic regions globally.This study provides crucial insights into the epidemiology, clinical characteristics, and outcomes of bronchopulmonary fungal infections in the Himalayan foothills. The high prevalence of invasive aspergillosis and antifungal resistance, underscores the need for vigilant clinical management and robust public health strategies to mitigate the impact of these infections.